2015
DOI: 10.3233/jad-141983
|View full text |Cite
|
Sign up to set email alerts
|

Apathy Treatment in Alzheimer’s Disease: Interim Results of the ASCOMALVA Trial

Abstract: The combination of donepezil with choline alphoscerate is more effective than donepezil alone in countering symptoms of apathy in AD. This suggests that the availability in brain of a higher amount of acetylcholine could affect apathy in AD subjects with spared executive functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
22
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 39 publications
4
22
0
2
Order By: Relevance
“…For clarity, the main characteristics of the ASCO-MALVA study are detailed below. Further details are reported in previous studies of our group [34][35][36]. Patients, diagnosed according to NINCDS-ADRDA criteria, were all in a mild/moderate-stage, showed brain ischemic lesions (in CT or MRI), and had at least two vascular risk factors (such as hypertension, diabetes, obesity, ischemic heart disease, hypercholesterolemia, hyperhomocysteinemia, smoking, previous cerebrovascular events, or family history of cardio-cerebrovascular diseases).…”
Section: Patients and Study Typementioning
confidence: 99%
“…For clarity, the main characteristics of the ASCO-MALVA study are detailed below. Further details are reported in previous studies of our group [34][35][36]. Patients, diagnosed according to NINCDS-ADRDA criteria, were all in a mild/moderate-stage, showed brain ischemic lesions (in CT or MRI), and had at least two vascular risk factors (such as hypertension, diabetes, obesity, ischemic heart disease, hypercholesterolemia, hyperhomocysteinemia, smoking, previous cerebrovascular events, or family history of cardio-cerebrovascular diseases).…”
Section: Patients and Study Typementioning
confidence: 99%
“…In the ASCOMALVA study, comparing a subgroup of AD individuals (n = 56) receiving a combination of donepezil and choline alphoscerate (a cholinergic precursor) versus a subgroup (n = 57) with donepezil alone (24-month treatment period), the combined treatment was more effective on apathy levels than donepezil alone (Rea et al, 2015;Carotenuto et al, 2017).…”
Section: Randomized Controlled Trials (Rct)mentioning
confidence: 99%
“…For some pharmacotherapies, including antipsychotic review, improvement of apathy was found only in combination with non pharmacological approaches. [40][41][42][43] As reviewed recently by Leong, 44 several randomized placebo-controlled interventions reported negative outcomes for antidepressant efficacy in dementia. Well-controlled studies, systematic reviews, and meta-analyses [45][46][47] have shown no reliable and convincing efficacy of antidepressants in patients with dementia and co-occurring depressive disorders.…”
Section: Introductionmentioning
confidence: 99%